Agonist-antagonist myoneural interface amputation preserves proprioceptive sensorimotor neurophysiology in lower limbs - Srinivasan, Shriya S. (Sci Transl Med, 2020)
The brain undergoes marked changes in function and functional connectivity after limb amputation. Agonist-antagonist myoneural interface (AMI) amputation is a procedure which restores physiological agonist-antagonist muscle relationships responsible for proprioceptive sensory feedback, to enable greater motor control. We compared results from the functional neuroimaging of individuals (n = 29) with AMI amputation, traditional amputation and no amputation. Individuals with traditional amputation demonstrated a significant decrease in proprioceptive activity, measured by activation of Broadman Area 3a (BA3a), whereas functional activation in individuals with AMIs was not significantly different from no amputation controls (p < 0.05). The degree of proprioceptive activity in the brain strongly correlated with fascicle activity in the peripheral muscles and performance on motor tasks (p < 0.05), supporting the mechanistic basis of the AMI procedure. These results suggest that surgical techniques designed to restore proprioceptive peripheral neuromuscular constructs result in desirable central sensorimotor plasticity.